Sludge stabilization: Characteristics of the end-products and an alternative evaluative methodology. (15th March 2020) - Mei, Xiaojie; Tang, Jianguo; Zhang, Yue
Graphical abstract: Highlights: Sixteen sludge treatment plants in China were investigated and analyzed. Complexity index and humic-like substances were proposed to evaluate the stabilization level. The humic-like substance contents in the end-products were 157.8–461.1 mg/gVS. Complexity index can predict the humification degree. Abstract: The treatment, disposal and resource recovery of sewage sludge is a major bottleneck for the water and environmental remediation efforts in China. In this paper, sixteen sludge treatment plants using anaerobic digestion and aerobic composting as stabilization procedures were investigated and analysed. The organic degradation rates varied from 0.5% to 80.2% of different plants, showing the close relationship with raw sludge property and treatment process. The increment rate of humic-like substances ranged from 19% to 81% in different cases. It has been aware of that stabilization procedures coupled the degradation of simple organics (proteins, polysaccharides, lipids) with the synthesis of complex organics (humic-like substances). Therefore, an alternative methodology, considering the content of humic-like substances (no less than 150 mg/gVS) and the fluorescence complexity index (up to 5.0) in the end-products, was proposed to evaluate the stabilization level. Humic-like substances indicate the ecological value of the end-products. Fluorescence complexity index, combining the reduction of protein-like substances with the increment of humic-like substances, can predict the humification degree. The new criterion can be the supplementary of the current ones.